Evaluation Patch of Rhizoma Extract Kencur (Kaempferia galanga L.) as Anti-Inflammatory with Enhancer - Hesti Riasari; Revika Rachmaniar; Sri Wahyuni (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Kencur (Kaempferia galanga L.) is a family of Zingiberaceae. Several studies have shown that kencur can help reduce inflammation because kencur is known to contain anti-inflammatory compounds, namely marker compounds from flavonoids, kaempferol. For the development of pharmaceutical preparations, research on anti-inflammatory plasters containing 96% ethanol extract, n-hexane extract, ethyl acetate extract and 70% ethanol extract from ginger rhizome with the addition of penetration enhancer (enhancer), namely propylene glycol. This anti-inflammatory plaster was tested for its activity in 5 groups of Wistar strain rat feet which had been induced 1% carrageenan (negative control); positive control (diclofenac sodium), ethanol96% extract, n-hexane extract, ethyl acetate extract and 70% ethanol extract from kencur rhizome and compared with plaster of kencur rhizome ethanol extract without enhancer. The results showed the effect of adding enhancers 30 minutes after administration. 96% ethanol extract and ethyl acetate extract had reduced inflammation by 79.99% in rat test animals compared to plaster ethanol extract of rhizome kencur without the addition of enhancers. Keywords :  Kaempferia galanga. L., patch, anti-inflammatory, enhancer, propylene glycol